Strategi Pemanfaatan Media Sosial sebagai Media Pembelajaran pada Program Kesetaraan Paket C di PKBM Melati - Alya Novita Kalili; Suparman; Arif Efendi A.S.; Saidang; Uli Nuha (Mataram University, 2026)
This study aims to explore and describe in-depth the form of social media utilization as a learning medium and its impact on the participation and learning motivation of learners in the Paket C Equivalency Program at PKBM Melati, Juppandang Village, Enrekang District. This study employs a qualitative approach with a descriptive research type to uncover the subjects' experiences naturally. Data collection was carried out through technical triangulation, namely participatory observation, in-depth interviews, and documentation, involving PKBM managers, tutors, and learners selected through purposive sampling. The results showed that the use of social media, specifically the WhatsApp and YouTube platforms, has transformed into the main instruments in implementing distance learning based on a blended learning approach. WhatsApp functions as a mobile-based Learning Management System (LMS) to distribute teaching materials, manage task submissions, and facilitate asynchronous discussions. Meanwhile, YouTube is strategically used as a supporting visual reference to facilitate the independent learning styles of adult learners. The use of social media provides a highly significant positive contribution, namely offering time flexibility for learners who are predominantly active workers, encouraging a transformation towards independent learning (self-directed learning), and effectively overcoming geographical distance barriers for residents living in remote areas. The main obstacles found in the field include internet network instability due to the hilly topography, digital literacy gaps among adult learners, and the economic burden of data quota costs. However, these various obstacles were successfully mitigated through the tutors' adaptive and humanistic policies by providing flexible deadlines for task completion, as well as the innovative involvement of the learners' family members in assisting with the use of technology. In conclusion, the integration of social media has proven effective as an andragogical solution in maintaining the continuity of participation and preserving the motivation of Paket C Equivalency Program learners amidst constraints of space, time, and infrastructure.